Comparison of Successful Principal Leadership Models (literature study in Indonesia and Finland) - Humairoh, Widya Belqis; Asy’ari, Hasyim (Universitas Wiralodra, 2024)
This article talks about successful principal leadership models in Indonesia and Finland. This research utilizes a qualitative approach through a literature study. This method allowed the researcher to explore and analyze various relevant sources of information related to the principal leadership model in both countries. This research is motivated by the differences in educational outcomes in the two countries, where the Finnish system is praised for its equity and inclusiveness, while Indonesia faces challenges in this regard. Understanding these differences is crucial to improving education practices and policies in Indonesia, which in turn can improve the overall quality of education and student success. This research is important because it provides insights into successful principal leadership models in Finland and Indonesia, which are known to have the best education systems in the world, and compares them with the situation in Indonesia which still faces many challenges. By understanding the best practices from Finland, this research can help Indonesia in formulating more effective education policies, improving teacher quality and creating a better learning environment. The research found the following results: Leadership Model In Finland: 1. democratic leadership model in Finland 2. pedagogical leadership model in Finland. Leadership Model in Indonesia: 1.Democratic leadership model in Indonesia 2.Transformational Leadership Model In Indonesia 3. Situational Leadership Model In Indonesia